2018
DOI: 10.1001/jamasurg.2017.4495
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Fluorodeoxyglucose F18–Labeled Positron Emission Tomography for Diagnosis of High-Risk Lung Nodules

Abstract: IMPORTANCE Clinicians rely heavily on fluorodeoxyglucose F18–labeled positron emission tomography (FDG-PET) imaging to evaluate lung nodules suspicious for cancer. We evaluated the performance of FDG-PET for the diagnosis of malignancy in differing populations with varying cancer prevalence. OBJECTIVE To determine the performance of FDG-PET/computed tomography (CT) in diagnosing lung malignancy across different populations with varying cancer prevalence. DESIGN, SETTING, AND PARTICIPANTS Multicenter retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…[ 18 F]FDG PET/CT has been demonstrated as a useful, yet incomplete, tool for lung nodules diagnosis. One of the main limitations is that many benign lesions also present high FDG uptake which can easily lead to falsepositive results [27,28] . SCC and solid nodules of AC showed high uptake of both [ 18 F]FDG and [ 68 Ga]Ga-DOTA-FAPI-04 because the solid components consist of densely packed tumor cells and peri-tumoral stroma, while GGO showed low uptake for lacking tumor cells and peri-tumoral stroma.…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 F]FDG PET/CT has been demonstrated as a useful, yet incomplete, tool for lung nodules diagnosis. One of the main limitations is that many benign lesions also present high FDG uptake which can easily lead to falsepositive results [27,28] . SCC and solid nodules of AC showed high uptake of both [ 18 F]FDG and [ 68 Ga]Ga-DOTA-FAPI-04 because the solid components consist of densely packed tumor cells and peri-tumoral stroma, while GGO showed low uptake for lacking tumor cells and peri-tumoral stroma.…”
Section: Discussionmentioning
confidence: 99%
“…PET-CT is a noninvasive and highly precise procedure to characterise SPNs with a reported sensitivity of up to 96–97% and a specificity of 85–88% [15]. PET-CT plays a crucial role in differentiating nodules >1 cm but, for those <1 cm, in single metastases in some types of malignancies or in benign diseases with increased FDG uptake, it is not conclusive [18, 24]. For nodules >8 mm, radiological imaging (CT and PET-CT) is usually accompanied by FNAB and even nodule resection.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a study by N omori et al [18], 90% of GGNs, finally diagnosed as well-differentiated adenocarcinomas, had a low metabolic uptake. Similarly, inflammatory nodules commonly present as ground-glass or subsolid attenuation, are often metabolically active, and lead to false-positive results [24].…”
Section: Diagnostics For Spnsmentioning
confidence: 99%
“…107 A multicenter study including 7 centers in North America concluded that PET/ CT has limited value to diagnose IPNs suspicious for lung cancer across a variety of clinical contexts, geographic regions and nodule sizes. 108 The overall sensitivity and specificity of FDG-PET to diagnose lung cancer was found to be 90.1% (95% CI, 88.1%-91.9%) and 39.8% (33.4%-46.5%), respectively. In the COSMOS screening study in 351 participants with 383 nodules, the overall sensitivity, specificity and accuracy of visually evaluated PET-CT in distinguishing malignant from benign nodules were 64% (95% CI 56-70%), 89% (83-93%) and 76% (71-80%), respectively.…”
Section: Q What Is the Role Of Pet/ct In Diagnosis Of Screening Ldctmentioning
confidence: 91%